The role of immune checkpoint blockade in uveal melanoma - Wessely, Anja; Steeb, Theresa; Erdmann, Michael; Heinzerling, Lucie; Vera, Julio; Schlaak, Max; Berking, Carola; Heppt, Markus (International Journal of Molecular Sciences, 2020)
Uveal melanoma (UM) represents the most common intraocular malignancy in adults and accounts for about 5% of all melanomas. Primary disease can be effectively controlled by several local therapy options, but UM has a high potential for metastatic spread, especially to the liver. Despite its clinical and genetic heterogeneity, therapy of metastatic UM has largely been adopted from cutaneous melanoma (CM) with discouraging results until now. The introduction of antibodies targeting CTLA-4 and PD-1 for immune checkpoint blockade (ICB) has revolutionized the field of cancer therapy and has achieved pioneering results in metastatic CM. Thus, expectations were high that patients with metastatic UM would also benefit from these new therapy options. This review provides a comprehensive and up-to-date overview on the role of ICB in UM. We give a summary of UM biology, its clinical features, and how it differs from CM. The results of several studies that have been investigating ICB in metastatic UM are presented. We discuss possible reasons for the lack of efficacy of ICB in UM compared to CM, highlight the pitfalls of ICB in this cancer entity, and explain why other immune-modulating therapies could still be an option for future UM therapies.
CRIS-Team Scopus Importer:2020-02-14
Keywords: CTLA-4; Cytotoxic T lymphocyte-associated antigen; Immune checkpoint blockade; Ipilimumab; Nivolumab; Ocular melanoma; PD-1; Pembrolizumab; Programmed death 1; Uveal melanoma